A constant border-crossing: Conversion and evangelical charismatic Christian identity among the Roma in Estonia and Latvia. Issue 1 (June 2020) - ROHT-YILMAZ, EVA-LIISA
Abstract : This article focuses on the interplay of (de)marginalization and identity building among evangelical Roma in Estonia and Latvia. The evangelization of the Roma, who are traditionally Orthodox, Lutheran, or Catholic, is conducted by Finnish Roma as part of their Eastern European outreach. I discuss the complexity of conversion and attempts to de-marginalize the Roma in Estonia and the Vidzeme region of Latvia. The narrative of de-marginalization turns out not to be the main reason to convert, and even converted Roma face the challenge of managing the tensions arising from having to follow several moral codes. Nevertheless, the way the converted Roma build their new more layered identity is still dependent on the narrative of de-marginalization.